Implementasi Green Marketing pada PT Yagi Natural Indonesia dalam Memasarkan Produk Perawatan Tubuh Ramah Lingkungan - Moza, Lygaya; Suryana, Asep; Trulline, Putri (Universitas Gajah Putih, 2024)
PT Yagi Natural Indonesia (Yagi Forest) is a company that produces environmentally friendly body care products from Indonesia which produces products made from organic ingredients that do not cause environmental pollution and do not have a negative impact on humans who use them. In promoting the environmentally friendly body care products produced, Yagi Forest does this through green marketing. This research aims to determine the implementation of green marketing carried out by Yagi Forest. This research uses a qualitative method with a case study approach and uses data collection techniques using in-depth interview techniques. The main informants in this research were two employees from Yagi Forest who worked in positions responsible for product marketing activities. The results of this research show that in its implementation Yagi Forest applies the green marketing mix concept, namely green product, green price, green place and green promotion. The products produced are products made from organic ingredients that are safe for consumers and the surrounding environment. Likewise, the product packaging used can be reused or returned to the collaborating organization so that it does not become waste that can damage the environment. Then in terms of price, products from Yagi Forest are relatively more affordable when compared to body care products from competing companies. Apart from that, promotional activities carried out use four basic activities from Integrated Marketing Communication (IMC), which is direct marketing, interactive/internet marketing, sales promotion, publicity/public relations. However, the implementation of the green place aspect cannot yet be carried out efficiently so an evaluation needs to be carried out.